2019
DOI: 10.15823/p.2018.132.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of school leadership style on effective teaching and teacher-student interaction

Abstract: The purpose of the study is to investigate the influence of school leadership on effective teaching and teacher-student interaction. A quasi-experimental research design, and a structured questionnaire were used in the study. A random cluster sample of teachers from lower secondary education were taken. The study demonstrated that a positive correlation exists between school leadership styles and effective teaching as well as teacher-students interaction. It can be concluded that the school leadership style im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Likewise, leadership goes beyond the narrow vision of the principal regarding administrative management (González-Falcón et al, 2020). The involvement of middle leaders and the community, driven shared clear vision in the school, promotion of trust within the school, inspiring teachers, and focus on teaching and learning allied to the use of information and school knowledge is conducive to effective leadership and quality of education (Andrews & Conway, 2020;Ezzani, 2015;González-Falcón et al, 2020;Rechsteiner et al, 2022;Tayag & Ayuyao, 2020;Xhomara, 2018). A new leadership arises from providing the whole community with opportunities to be more active in applying innovation and brokering strategies to build competencies for continuous improvement.…”
Section: A 'New' Leadership To Play In An Accountable Systemmentioning
confidence: 99%
“…Likewise, leadership goes beyond the narrow vision of the principal regarding administrative management (González-Falcón et al, 2020). The involvement of middle leaders and the community, driven shared clear vision in the school, promotion of trust within the school, inspiring teachers, and focus on teaching and learning allied to the use of information and school knowledge is conducive to effective leadership and quality of education (Andrews & Conway, 2020;Ezzani, 2015;González-Falcón et al, 2020;Rechsteiner et al, 2022;Tayag & Ayuyao, 2020;Xhomara, 2018). A new leadership arises from providing the whole community with opportunities to be more active in applying innovation and brokering strategies to build competencies for continuous improvement.…”
Section: A 'New' Leadership To Play In An Accountable Systemmentioning
confidence: 99%
“…"The transformational and transactional leadership scales, as well as amount of students' study time, correlated significantly with innovation climate, affiliation, principal positions in schools, and collaborative activity at both the teacher and the school levels and academic achievements of students" (Oterkiil & Ertesvåg, 2014;Gipson, Pfaff, Mendelsohn, Catenacci & Burke, 2017;Xhomara & Hasani, 2018); meanwhile, Bogler (2001) revealed that "principals' transformational leadership affected teachers' satisfaction both directly and indirectly through their occupation perceptions". "There is a moderate, positive and significant relationship between transformational leadership, lectures attendance, and overall teachers' job satisfaction and academic achievements" (Tadele, 2014;Xhomara, 2017); and "teachers' perceptions of supportive leadership are closely linked with transformational and distributed leadership" (Mancuso, Roberts & White, 2011). So, there is a little gap in the literature examination about the relationship connecting school leadership models and the educational performance of teachers.…”
Section: Figure 1 the Conceptual Foundation Of Contingent And Postmod...mentioning
confidence: 99%
“…According to Mombourquette (2017), vision is the vital element in effective leadership. Xhomara (2018), drawing on the work of Bennis and Nanus (1985), ten emerging generalizations about leadership, four of which are directly related to vision. a) Outstanding leaders have a vision for their organization b) The vision must be communicated in a way that secures commitment among members of the organization.…”
Section: Vision In Leadershipmentioning
confidence: 99%